Struktur Kepribadian Nabi Yunus dalam Alqur'an (Pendekatan Psikoanalis Sigmund Freud): (Pendekatan Psikoanalis Sigmund Freud) - Qurratul Aini (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2021)
The Qur'an is not only seen as an ordinary text, it can also be considered a literary text. So that literary research in the Al-Quran has become commonplace and is often done. The narrative method in the Al-Qur'an is considered the most appropriate method for conveying messages, and Sigmund Frreud's literary psychological theory can perfect the method of conveying messages in stories. Because this theory is in direct contact with the reader's soul, and can reproduce itself through the characters. The purpose of this research is to describe the personality structure of the prophet Yunus in the Al-Qur’an, where the personality structure offered by Freud consist of the id, ego, and superego. The method used in this research is descriptive qualitative, namely by describing the facts as they are. The data collection method is by using note-taking and listening techniques, which are collected based on the Al-Qu'an verse as the main object and the research library as the supporting object. The result of this research is that the personality structure possessed by the Prophet Yunus only consists of the id, ego and the superego, but the most dominant personality possessed by the Prophet Yunus is the Superego, namely how the nature of morality awakens him from the mistakes he has made. This cannot be separated from the ability of Allah's hand, because remembering that the Prophet Yunus was a pious messenger of Allah who was sent to a people. Apart from the personality structure, Prophet Yunus also carried out the ego defense mechanism. Ego defense mechanisms in this study are apathy and sublimation.